A natural depsipeptide antibiotic binds the E-site of the bacterial ribosome - Manpreet Kaur; Dmitrii Y. Travin; Max J. Berger; Manoj Jangra; Martino Morici; Haaris A. Safdari; Dorota Klepacki; Wenliang Wang; Michael Cook; Sommer Chou; Allison K. Guitor; Kalinka Koteva; et al. (Nature, 2026)
Abstract A key challenge in addressing the antibiotic resistance crisis is identifying new antimicrobial compounds 1 . Although natural products produced by fungi and bacteria, particularly actinomycetes, have been the source of most antibiotics discovered over the past 80 years, they have fallen out of favour owing to the frequent rediscovery of known drug scaffolds 2 . The current perception is that antibiotic-producing actinomycetes have been over-mined and possess little novelty left to yield. Here we demonstrate that by using improved fractionation approaches that enrich previously overlooked minor products, even well-studied strains of antibiotic-producing actinomycetes can provide new chemical scaffolds with unique modes of action. By fractionating a library of natural product extracts from soil bacteria, we show that Streptomyces rimosus , the source of the well-known antibiotic oxytetracycline, produces a cyclic depsipeptide antibiotic that we call manikomycin. Manikomycin can kill multidrug-resistant Enterobacteriaceae and is not susceptible to resistance associated with clinically used antibiotics. Biochemical, genetic and structural analyses reveal that manikomycin binds in the E-site of the large subunit of the bacterial ribosome, preventing entry of the 3′ end of the tRNA into the E-site and effectively hindering the translocation step of protein synthesis in a sequence-context-specific manner. Manikomycin is the first antibacterial agent, to our knowledge, to target the critical but underexplored E-site in the large ribosomal subunit, highlighting its value as a lead for developing new antibiotics.